1. rozwiąż równanie:

a) x√2-3=x
b) x+(1+x)√5=1
c) (x-3)(x+4)-2(3x-2)=(x-4)²
d) 5(x-1)²-2(x+3)²=3(x+2)²-7(6x-1)
e) 3(x+1)²+(x-4)³=101+(x-3)³

2. rozwiąż układ równań:

a)
2x+5y=26
3x-2y=1

b)
4x-y=18
5x+2,5y=30

c)
√2x+√3y=√3+2
x-2√2y=-√2

3. Rozwiąż równanie:

a) (3x-1)(4x+5)=(4x+5)(2x-1)
b) 51-y(3y+4)=2(17-2y)-58
c) (2+5x)²=19x+(x-4)(x+5)
d) 25(x-1)²-9(x+2)²=0
e) 3x²-2√3x-3=0
f) (x+3)²-5(x+3)+4=0

2

Odpowiedzi

2009-12-08T23:25:55+01:00
2x+5y=26
3x-2y=1
2x=26-5y/2
x=13-5/2y
3(13-5/2y)-2y=1
39-15/2y-2y=1
39-7 1/2y-2y=1
-9 1/2y=1-39
-19/2y=-38/razy (-2)
19y=38/19
y=2
x=13-5/2 y
x=13-5/2 razy2
x=13-5
x=8
1 5 1
2009-12-08T23:58:02+01:00
. rozwiąż równanie:

a) x√2-3=x
x√2-x=3
x(√2-1)=3
x=3/(√2-1)

b) x+(1+x)√5=1
x+√5+√5x=1
x(1+√5)=1
x=1/(1+√5)

c) (x-3)(x+4)-2(3x-2)=(x-4)²
x²-3x+4x-12-6x+4=x²-8x+16
x²-x²-5x+8x=16-4+12
3x=24
x=8

d) 5(x-1)²-2(x+3)²=3(x+2)²-7(6x-1)
5(x²-2x+1)-2(x²+6x+9)=3(x²+4x+4)-42x+7
5x²-10x+5-2x²-12x-18=3x²+12x+12-42x+7
5x²-2x²-3x²-22x-13-12x+42x=19
10x=6
x=6/10
x=0,6


e) 3(x+1)²+(x-4)³=101+(x-3)³
3(x²+2x+1)+(x-4)(x²-8x+16)=101+(x-3)(x²-6x+9)
3x²+6x+3+x³-4x²-8x²+32x+16x-64=101+x³-3x²-6x²+18x+9x-27
x³-x³+3x²-4x²-8x²+3x²+6x²+6x+32x+16x-18x-9x=64-3-27
27x=34
x=34/27

2. rozwiąż układ równań:

a)
2x+5y=26
3x-2y=1
2x=26-5y
x=13-2,5y
3(13-2,5y)-2y=1
39-7,5y-2y=1
-9,5y=-39+1
-9,5y=-38
y=4
2x+5*4=26
2x+20=26
2x=26-20
2x=6
x=3

b)
4x-y=18
5x+2,5y=30
-y=-5x+18
y=5x-18
4x-y=18
4x-5x+18=18
-x=0
x=0
y=5*0-18
y=-18


c)
√2x+√3y=√3+2
x-2√2y=-√2
x=-√2+2√2y
√2(-√2+2√2y)+√3y=√3+2
-2+4y+√3y=√3+2
4y+√3y=√3+2+2
y(4+√3)=√3+4
y=(√3+4)/(4+√3)
y=1
x=-√2+2√2*1
x=√2

3. Rozwiąż równanie:

a) (3x-1)(4x+5)=(4x+5)(2x-1)
12x²-4x+15x-5=8x²+10x-4x-5
12x²-8x²-4x-10x+4x-5+5=0
4x²-10x=0
Δ=b²-4ac=100-0=100
√100=10
x₁=(-b-√Δ)/2
x₁=(-10-10)/2
x₁=-10
x₂=(-b+√Δ)/2
x₂=(-10+10)/2
x₂=0

b) 51-y(3y+4)=2(17-2y)-58
51-3y²-4y=34-4y-58
-3y²-4y+4y+51-34+58=0
-3y²+75=0
Δ=b²-4ac=0+900=900
√900=30
x₁=(-b-√Δ)/2
x₁=(0-30)/2
x₁=-15
x₂=(-b+√Δ)/2
x₂=(0+30)/2
x₂=15


c) (2+5x)²=19x+(x-4)(x+5)
4+20x+25x²=19x+x²-4x+5x-20
25x²-x²+20x-19x+4x-5x+20-4=0
24x²+16=0
Δ=b²-4ac=0+1536=1536

x₁=(-b-√Δ)/2
x₁=(0-√1536)/2
x₁=-√1536/2
x₂=(-b+√Δ)/2
x₂=(0+√1536)/2
x₂=√1536/2



d) 25(x-1)²-9(x+2)²=0
25(x²-2x+1)-9(x²+4x+4)=0
25x²-50x+25-9x²-36x-36=0
16x²-86x-9=0
Δ=b²-4ac=7396-576=6820

x₁=(-b-√Δ)/2
x₁=(86-√6820)/2

x₂=(-b+√Δ)/2
x₂=(86+√6820)/2


e) 3x²-2√3x-3=0
Δ=b²-4ac=12+36=48
x₁=(-b-√Δ)/2
x₁=(2√3-√48)/2

x₂=(-b+√Δ)/2
x₂=(2√3+√48)/2


f) (x+3)²-5(x+3)+4=0
x²+6x+9-5x-15+4=0
x²+x-2=0
Δ=b²-4ac=1+8=9
√Δ=3
x₁=(-b-√Δ)/2
x₁=(-1-3)/2
x₁=-4/2=-2
x₂=(-b+√Δ)/2
x₂=(-1+3)/2
x₂=2/2=1


1 5 1